Evaluación preliminar del aceite de Palo de Rosa (Aniba rosaeodora Ducke) como desinfectante natural en superficies no porosas - Aguirre Tapullima, Roxana Prissilla (2025)
Chemical disinfectants, although effective against pathogenic microorganisms, can have adverse effects on human health and food safety. This experimental research with a completely randomized and factorial design evaluated the antimicrobial efficacy of Aniba rosaedora (rosewood) essential oil as a natural disinfectant. Antimicrobial activity was evaluated by disk diffusion, MIC and MBC against 6 bacterial strains, using concentrations of 3000 to 1000 mg/mL for disk diffusion and 32 to 0.25 mg/mL for MIC. Bactericidal activity was then evaluated by quantitative suspension and non porous surface assays, with concentrations of 128, 160 and 320 mg/mL and contact times of 5, 10 and 15 minutes, in clean and dirty conditions, against two bacterial strains. The disk diffusion results show that S. aureus and S. Typhimurium were sensitive to the concentrations studied, while the others, except P. aeruginosa (resistant), showed intermediate activity. The MIC and MBC for S. aureus and S. Typhimurium were 2 and 4 mg/ml respectively. The quantitative suspension test showed disinfectant activity against S. aureus and E. hirae with an average value of 4 and between 3 and 4 for the three times and in dirty and clean conditions respectively. The quantitative test on a non-porous surface demonstrated high efficacy against S. aureus and E. hirae at concentrations of 160 and 320 mg/mL, observing logarithmic reductions of 7.67 and 7.54, respectively, for both bacteria in clean and dirty conditions. These results indicate a powerful disinfectant activity of rosewood essential oil on smooth surfaces.